(untitled) (Research, Society and Development, 2022)
This research has the general objective of analyzing the impacts that the municipality of Sertânia-PE suffered from the floods in March 2020 and the action of public management in the prevention and mitigation of disasters. As specific objectives, it is proposed: 1. Carry out a survey on the impacts that the municipality has suffered of an economic and social nature; 2. Analyze the performance of municipal public management in the prevention and mitigation of disasters; 3. Present a diagnosis on how the municipality acted in the face of floods that occurred in 2020. This work was carried out observing, mainly, the concepts about disasters and disaster risk management presented in the literature and national legislation. This is a case study, being a work of a qualitative nature where, in order to fulfill the objectives, searches for information were carried out in municipal secretariats and official websites of the city hall and an exploratory analysis of municipal documents was carried out. Faced with the heavy rains of the period studied, the absence of risk and disaster management, seeking prevention for the studied municipality, generated impacts that could be avoided or mitigated, in the same way, when presenting how the municipality acted before and especially after the disaster that occurred, the importance of implementing disaster prevention and mitigation actions is demonstrated. It is possible to understand the crucial role of municipal entities in the prevention and mitigation of disasters, in addition, it emphasizes the importance, need and urgency of municipalities to implement risk and disaster management in their localities, considering the environmental and climatic scenario in which we live.